Exogenous leptin increases lipid peroxidation in the mouse brain - Kutlu, S; Canpolat, S; Aydin, M; Yasar, A; Tuzcu, M; Baydas, G (Tohoku Univ Medical Press, 2005)
Leptin, a hormone produced by the adipose tissues, reduces appetite and food intake, and increases energy expenditures by sending signals to the brain cells. As human obesity is associated with hyperleptinemia and increased systemic oxidative stress, we investigated whether leptin affects lipid peroxidation and antioxidant status in the brain. Leptin was intraperitoneally administered to adult male BALB/c mice (n = 6) at a dose of 40 mu g/animal for 5 days, while control mice (n = 6) received phosphate buffered saline. All animals were decapitated one hour after the last injection, and the brain tissues were removed. Total brain tissues were homogenized with phosphate buffered saline. Lipid hydroperoxide and glutathione levels were measured by enzyme immunoassays. Data were statistically analysed by using Mann Whitney's U-test. Lipid hydroperoxide levels were significantly higher in the brain tissue of leptin-treated mice (3.44 +/- 0.36 nmol/g tissue, mean +/- S.E.M.) than those of the control mice (2.20 +/- 0.38 nmol/g tissue, p < 0.01). In contrast, leptin-treated mice had significantly lower glutathione levels in the brain tissue compared to the control (12.97 +/- 1.32 and 17.91 +/- 0.82 nmol/g tissue, respectively, p < 0.05). These results indicate that exogenous leptin increases lipid peroxidation and inhibits antioxidant system in the mouse brain. We therefore suggest that leptin may augment oxidative stress in the brain. (c) 2005 Tohoku University Medical Press.
Keywords: leptin; lipid peroxidation; brain and mouse